THE THINKING DECENTRALIZATION AND RUN-AND-CATCH GAMES IN PHYSICAL EDUCATION CLASSES (Fiep Bulletin - online, 2014)
The aim of this study was to evaluate the possibility to estimate children's decentralization process, focusing the necessity to give them opportunity to reflect about their actions. Thirty children were randomly selected, all between 5 and 6 years old, from two city schools: E. M. Frei Florentino and E. M. Francisca Alegretti, in Muzambinho - MG. They were divided in three groups with ten children each ( A, B and C ) each group with different activities. Groups A and B, with two 60-minute classes per week, were assigned identical run-and-catch games. In group A, appropriate strategies allowed the children to exchange ideas, elaborate rules, find out different run and catch strategies and make decisions. In group B the games were played without concerns of creating an appropriate environment in order to allow the children to think about their actions. No special activity was suggested to group C. The children from groups A and B were observed during a game session conducted as follows: each group of four children played for a one-minute period, three fugitives and a catcher. The game was repeated with a different catcher until all four played the catcher role. The results showed that all children belonged to level 1 since they were always trying to catch the same fugitive and constantly confused the roles of catcher and fugitive. After three months, the children were observed again. Group A, with better results, confirmed the need to create situations where the children reflect about their actions, contributing to the decentralization process. As for group B, it was clear the fragility of the results, compared to the control group, confirming the need to stimulate children to reflect about what they do.
Keywords: physical education; run-and-catch games; decentralization